(untitled) (Kerala Journal of Psychiatry, 2021)
Meta-analysis is a study design that assesses previous research quantitatively and arrives at a conclusion for a research question; that outcome or conclusion is considered strong enough to be kept in an apex position in the hierarchy of evidence. Meta-analysis is found to be a hurdle for most novice researchers due to complex statistical procedures and the availability of unbiased published literature globally. The lack of accurate theoretical background also adds to the aforementioned complexity. This paper tries to portray a simple, practical outline about meta-analysis, justification for using this design, other essential aspects concerned and methods to be used. Literature relevant to the topic published within ten years in prominent journals and websites has been reviewed thoroughly while writing this paper. Keywords used for literature search were; ‘Meta-analysis’, ‘systematic review’, ‘Meta-analysis research design’ and ‘Meta-analysis framework’. The search was carried out after applying appropriate Boolean operators. Thoroughly and rigorously conducted meta-analysis is valid and has the potential of decision making in evidence-based medicine practice as it provides a more precise and cumulative estimate of the effect of a treatment/intervention, risk factor for a disease and or efficacy of drugs. The necessity to inculcate results or findings from numerous research studies makes it clear that meta-analysis as a research design is desirable in the field of medicine.